LiaS gene from two-component system is essential for caries pathogenicity in dual-species biofilms of Streptococcus mutans and Candida albicans - Cao, Yanfan; Zeng, Yu; Yang, Yuze; Gan, Guowu; Chen, Shuai; Huang, Xiaojing (Frontiers in Microbiology, 2025)
IntroductionThis study elucidated the critical role of the liaS gene in the Streptococcus mutans (S. mutans) two-component signal (TCS) transduction system during cross-kingdom interactions with Candida albicans (C. albicans). This gene governs the cariogenic potential of dual-species biofilms.MethodsGene expression analysis of cocultured samples was performed. The survival rate during H2O2 treatment in single and dual-species was assessed. Bacterial adhesion, extracellular polysaccharide (EPS) synthesis, acidic metabolite accumulation, and early adhesion of C. albicans in dual-species biofilms were evaluated.ResultsCompared with the wild-type (WT) and complemented strains (liaS–-comp), liaS- exhibited impaired acid tolerance due to downregulated comDE expression. The liaS knockout mutant strain also presented reduced vicRK expression, leading to diminished glucosyltransferase (Gtf)-mediated bacterial adhesion, EPS synthesis, and acidic metabolite accumulation. Although C. albicans alleviated oxidative stress by secreting superoxide dismutase, liaS- markedly compromised the intracellular reactive oxygen species (ROS) scavenging capacity and reduced the survival rate during H2O2 treatment in single and dual-species. Furthermore, liaS- inactivation suppressed the early adhesion of C. albicans in dual-species biofilms by reducing the synthesis of cyclic adenosine monophosphate (cAMP).ConclusionThis work provides the first evidence that liaS orchestrates a multidimensional phenotypic regulatory network that coordinately modulates biofilm architecture and metabolic activity. This activity ultimately attenuates cariogenicity in vivo, thus highlighting liaS as a pivotal virulence determinant in cross-kingdom infections and emphasizing its potential as a therapeutic target against dental caries.